PENGARUH PERSEPSI HARGA, KUALITAS DAN DESAIN PRODUK, DAN AKTIVITAS PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT. KENCANA INDAH PLASTIK INDONESIA (KIPI) - Petrus Rangga Susanto, 08.05.51.0031; Marlien, R.A (Students Journal of Economic and Management, 2013)
The era of globalization is causing a variety of changes in both the physical environment, social, economic, political, marked by progress in science and technology very rapidly. This condition affects an increasingly open market and competition is growing rapidly, which is more critical and intelligent consumers choose and evaluate a product and will ultimately memnutuskan purchase the product. The purpose of this research is to analyze the effect of price perception, product quality, product design and promotional activities of the purchasing decisions in the PT. Plastic Kencana Indonesia Indah (KIPI) The population in this study were all customers of PT. Beautiful Plastic Kencana Indonesia Semarang 236 as customers, with the number of samples obtained with 70 respondents sampling purposive sampling method. The type of data used is primary data, using the method of data collection questionnaire distribution. The analysis toolÂ used is multiple regression. The results of this study are: price perception positive influence purchasing decisions. Quality products positive influence purchasing decisions. Product design positive influence purchasing decisions. Promotional Activities positive influence on purchase decisions.Key words: Perceptions of Price, Quality and Product Design, Promotional Activities, Purchase Decision